The Role of Demographic Characteristics in the Development Process in Karbala Governorate - الموسوي مروه فاضل عبيد; الاعرجي‌ مروه حسين علي (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The relationship between development and population is interconnected, which is why this research aims to demonstrate the link between population and development in Karbala Governorate. This issue was studied and hypotheses were formulated by dividing the research into three sections. The first section addresses the theoretical framework of the study, while the second section examines demographic characteristics and their role in development in Karbala Governorate. The third section explores demographic influences and their impact on development, with a particular focus on:- The young working-age population (15-65 years) as the productive segment. - The younger age groups (under 15 years) as future resources that can significantly advance development. Therefore, it is essential to identify and analyze the effects of population variables on the development process. Planners and policymakers must make appropriate decisions and adopt suitable population policies that align with developmental objectives.